Ekologija plemenitilnih procesov: Navodila za vaje - Ojstršek, Alenka (University of Maribor Press, 2022)
Ecology of Finishing Processes: Exercise Instructions. A special problem of waste in the textile industry represents technological wastewaters, especially those generated during textile finishing. These wastewaters are heavily contaminated, contain various chemicals and textile auxiliaries, have extreme pH values and high COD and BOD values, contain various types of organic dyes that cause coloration, phosphates, sulphates and other salts, surfactants, fats and oils and different types of heavy metals. Textile wastewaters are very heterogeneous in composition; therefore, their treatment is very complex, and there are still no ideal and pre-designed method. Depending on the production process, it is necessary to choose a flexible and economically justified treatment technology. Herein, we must take into account wastewater’ quantity and quality, which is evaluated by means of basic and specific ecological parameters.